Ageing and Employment Prospects: The Case of Slovenian Unemployed Workers - Redek, TjaÅ¡a; SuÅ¡jan, Andrej (Mediterranean Journal of Social Sciences, 2012)
The paper analyzes the perceptions of older unemployed in Slovenian labour market. The empirical results are basedon a survey, which was conducted in April 2009. The results show that even 52 % of older unemployed workers believe that theyhave been victims of age discrimination. They believe that age is a disadvantage when seeking work. The consequences ofperceived discrimination are most often that the individuals do not apply for a job, because they feel that they would not bechosen, a highly undesirable result in an ageing population. The analysis is one of the few of its kind in the region. It also offersimportant policy conclusions and potential for future research.